PENGOPTIMALAN DAYA MENGGUNAKAN METODE SECANT PHOTOVOLTAIC STATIS - Riny Sulistyowati; Joko Ramatulloh (Universitas Nusa Cendana, 2022)
A solar panel is a series of photovoltaic cells that converts sunlight into electrical energy. The solar panel can work optimally during daytime because the output power depends on the light intensity, temperature and load contained in the solar panel. Therefore an algorithm of Maximum Power Point Tracker (MPPT) is required as a storage control in order to obtain the maximum output power using secant method. This method is one of the methods used to find the root value of an equation, i.e. by taking sampling of an equation that will be used to assess the equation root by applying the slope estimate differentiation. The result of this method was used to set up the duty cycle utilizing DC-DC buck converter. Duty cycle was set at 50% with a duration of 0.25 seconds, functioned to regulate the output voltage of the solar panel in order to be in maximum position which does not exceed 14 V. At the peak position the tracking was slightly constrained by reading output voltage from the solar panel to calculate the new value. Thus, the output of the solar panel would follow the output of solar panel in order to be at the maximum point